Implementation of Digital-Based Public Service Policies at The Metro Jaya Police Directorate of Intelligence and Security: A Study of Online Police Record Certificates - Caroline Yulia Kusuma; Nuraisyah Ambo; Rivai, Abdul (Journal of Public Administration and Government, 2025)
This research aims to analyze the implementation of digital public service policy in issuing Police Record Certificates (SKCK) at the Directorate of Intelligence and Security (Ditintelkam) of the Jakarta Metropolitan Police (Polda Metro Jaya). The Online SKCK service is a digital innovation initiated by the Indonesian National Police to enhance public service quality by promoting faster, more transparent, and accountable processes through the Super App Presisi POLRI application. This study employs a qualitative descriptive approach using in-depth interviews, observations, and document analysis with relevant stakeholders. Data were analyzed based on George C. Edwards III’s policy implementation theory, which consists of four variables: communication, resources, disposition, and bureaucratic structure. The findings reveal that the implementation of the Online SKCK policy at Polda Metro Jaya is not yet optimal. The main obstacles include insufficient public dissemination, limited human resource capacity in digital access, and weak inter-agency coordination. Nevertheless, there is a strong institutional commitment to improve the system through infrastructure enhancement, personnel capacity development, and information system integration. This study provides strategic recommendations to strengthen coordination, expand outreach, and improve the overall effectiveness of digital public service delivery within the police institution.